Amphiphilic Lignin Nanoparticles Made from Lignin-Acrylic Acid-Methyl Methacrylate Copolymers - Yingchao Wang; Niloofar Alipoormazandarani; Lauren Skye Puumala; Weijue Gao; Shanshan Liu; Fangong Kong; Qiang Wang; Pedram Fatehi (Nanomaterials, 2022)
In this study, a novel amphiphilic KL-AA-MMA nanoparticle was prepared through the graft copolymerization of kraft lignin (KL) with acrylic acid (AA) and methyl methacrylate (MMA), using potassium persulfate as an initiator in a water/dimethyl sulfoxide solvent medium, which was followed by the nanoprecipitation technique using dimethylformamide as a solvent and deionized water as an antisolvent. The successful graft polymerization was verified by 1H-nuclear magnetic resonance (NMR), 31P-NMR, and Fourier transform infrared (FTIR) analyses; and the grafting yield of the generated KL-AA-MMA copolymer ranged from 68.2% to 96.5%. Transmission electron microscopy (TEM) observation revealed the formation of amorphous KL-AA-MMA nanoparticles. Additionally, KL-AA-MMA9 nanoparticles with the highest yield exhibited the minimum hydrodynamic diameter and polydispersity of 261 nm and 0.153, respectively. Moreover, the amphiphilicity of KL-AA-MMA nanoparticles was significantly improved by the grafting of MMA monomers. Finally, the adsorption performance of KL-AA-MMA nanoparticles at the xylene interface was evaluated by a quartz crystal microbalance with dissipation (QCM-D). The results demonstrated that the most amphiphilic sample, KL-AA-MMA9 nanoparticles, with the smallest hydrodynamic size displayed the highest adsorption on the oil/water interface. This product provides a wide range of applications in oil/water emulsions.